Development of Contextual Worksheet Based on Characteristics of SPLDV Material at SMP Negeri 2 Bumi Nabung - Antika Wijayanti; Selvi Loviana (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
Learning mathematics requires learning media that are interesting and contain contextual life history. This study aims to develop valid, practical, and contextual worksheets which contain illustrated stories (comic) with characters. This worksheet uses Systems of Linear Equations in Two Variables material. The type of research used in this study is Research and Development. The research procedure used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The tryout was conducted on a small-scale group involving fifteen class VIII D SMP Negeri 2 Bumi Nabung students. The results showed that the validation of material experts obtained a total average of 3.45 with the validation criterion of "Valid." The results of the media expert validation obtained a total average of 3.86 with the validation criterion of "Valid." The student response questionnaire analysis results obtained a total score percentage of 92% with the practicality criterion "Very Practical." The results of this study indicate that the worksheet developed has met the criteria and is practical, so the worksheet is suitable for use in learning. Keywords: Development, Worksheet, Contextual, Comic